2005
DOI: 10.1093/ps/84.4.587
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of broiler performance when fed diets containing corn grain with insect-protected (corn rootworm and European corn borer) and herbicide-tolerant (glyphosate) traits, control corn, or commercial reference corn

Abstract: A 42-d feeding experiment with growing Ross x Ross 508 broilers showed that the nutritional value of insect-protected and herbicide-tolerant corn was comparable to that of the genetically similar control and 5 commercial reference corn hybrids. MON 88017 provides protection from feeding damage by coleopteran pest corn rootworm and is tolerant to the action of glyphosate, the active ingredient in the Roundup family of agricultural herbicides. MON 88017 x MON 810 was developed by the traditional breeding of MON … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 3 publications
2
5
0
Order By: Relevance
“…Meat sample analysis showed a lower protein and higher fat content in the thigh meat samples as compared to breast meat (Table 3), as also reported by Taylor et al (2005), in broilers fed on corn-soy diet. However, different levels of flaxseed in the diet did not affect the protein, fat and ash content of breast and thigh meat samples.…”
Section: Carcass Yield and Qualitysupporting
confidence: 80%
“…Meat sample analysis showed a lower protein and higher fat content in the thigh meat samples as compared to breast meat (Table 3), as also reported by Taylor et al (2005), in broilers fed on corn-soy diet. However, different levels of flaxseed in the diet did not affect the protein, fat and ash content of breast and thigh meat samples.…”
Section: Carcass Yield and Qualitysupporting
confidence: 80%
“…The broiler chicken model has been used in nutritional equivalency evaluations with whole grains and processed fractions from GM plants because of their rapid growth and reported sensitivity to nutritional deficiencies. Many broiler chicken feeding trials conducted with crops from insect-resistant, herbicide-tolerant, or stacked trait grains reported no differences in nutritional performance and carcass variables between broilers consuming diets formulated with grains or processed fractions from transgenic crops and those consuming diets with nontransgenic grains or processed fractions (Brake and Vlachos, 1998;Brake et al, 2003Brake et al, , 2005Taylor et al, 2003aTaylor et al, ,b,c, 2004Taylor et al, , 2005Taylor et al, , 2007McNaughton et al, 2007a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Production studies with monogastric livestock POULTRY Numerous feeding studies with day-old broiler chicks and laying hens have now been reported (Brake and Vlachos, 1998;Gaines et al, 2001a;Stanisiewski et al, 2002;Taylor et al, 2002Taylor et al, , 2003Taylor et al, , 2004Taylor et al, , 2005Brake et al, 2003;Elangovan et al, 2003;Kan and Hartnell, 2004a,b). The diets were all formulated to contain a high proportion of the test material which included GM varieties of Bt and Ht maize, soybean, canola and wheat, and appropriate counterparts.…”
Section: Nutrient Bioavailabilitymentioning
confidence: 99%